Coating self-repairing method for hydrogen conveying pipeline and application

CN119876827APending Publication Date: 2025-04-25CHINA PETROLEUM & CHEMICAL CORP +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311392109.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-25
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

Due to the hydrogen embrittlement phenomenon, the existing pure hydrogen pipeline can only use low-strength steel, which has low hydrogen transmission efficiency and short life. The existing technology has problems such as short coating life, high cost, and difficulty in large-scale application.

Method used

Aluminum coating and alumina coating are prepared in sequence from inside to outside on the outer surface of the welded area of ​​the hydrogen transport pipeline to form a self-healing hydrogen-resistance coating, and hydrogen doped oxygen is introduced during the hydrogen transport process to start the self-healing process.

Benefits of technology

Through the synergistic effect of self-healing hydrogen-resistance coating and oxygen-doped hydrogen, the hydrogen embrittlement resistance of the hydrogen transport pipeline is significantly improved, the fatigue life is extended, the cost is reduced, and the service life is achieved up to 50 years.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119876827A_ABST
    Figure CN119876827A_ABST
Patent Text Reader

Abstract

The invention provides a coating self-repairing method for a hydrogen conveying pipeline and application of the coating self-repairing method. According to the method, an aluminum coating and an aluminum oxide coating are sequentially prepared on the outer surface of a welding area (including a welding seam and a welding heat affected zone) of the hydrogen conveying pipeline from inside to outside, and the self-repairing hydrogen-resisting coating is formed; and then in the actual hydrogen conveying process of the hydrogen conveying pipeline, oxygen-doped hydrogen is conveyed into the hydrogen conveying pipeline, and the self-repairing process is completed. According to the method provided by the invention, the self-repairing hydrogen-resistant coating is only constructed on the outer surface of the welding area most sensitive to hydrogen embrittlement in the hydrogen transmission pipeline, and the service life of the whole hydrogen transmission pipeline system can be greatly prolonged by combining the input of oxygen-doped hydrogen, so that the area of the self-repairing hydrogen-resistant coating needing to be constructed is greatly reduced, and the production cost is reduced. And the hydrogen embrittlement prevention cost of the hydrogen conveying pipeline system is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of pure hydrogen pipeline transportation safety, and in particular relates to a coating self-repairing method for a hydrogen pipeline and its application. Background Art

[0003] Generally, hydrogen can be divided into gray hydrogen, blue hydrogen and green hydrogen according to the way it is obtained. Among them, gray hydrogen refers to hydrogen produced using fossil energy such as coal and oil. During the production process, a large amount of greenhouse gases such as carbon monoxide and carbon dioxide will be produced, which will cause air pollution problems; blue hydrogen refers to the production of hydrogen using industrial by-products; green hydrogen refers to hydrogen produced by converting renewable energy into electricity and using this electricity to electrolyze water. Since the production process of green hydrogen involves almost no carbon emissions, under the influence of factors such as fossil energy shortages, carbon tax growth, and environmental pollution, green hydrogen will gradually have a price competitive advantage, and it is expected to be used on a large scale after 2030. However, one of the characteristics of green hydrogen is that oxygen is produced during the production process, and the utilization of oxygen in green hydrogen is a difficult problem that needs to be solved urgently.

[0004] In order to meet the equipment requirements for large-scale hydrogen production, storage and transportation, welding processing is an inevitable processing technology. However, typical thermal cycle characteristics such as high heat input during welding make the welding area different from the parent material in terms of microstructure, which is bound to affect its sensitivity to hydrogen embrittlement. Usually, the grains in the heat-affected zone of the weld are larger, which facilitates the penetration and diffusion of hydrogen atoms, causing the welding area to become a sensitive area of ​​hydrogen embrittlement of the material. Due to the influence of hydrogen embrittlement, the existing pure hydrogen pipeline can only use low-strength steel as the pipeline material, and the pressure requirements for hydrogen transportation are strict, the hydrogen transportation efficiency is low, and the hydrogen embrittlement phenomenon also seriously restricts the life of the pipeline. The existing technology for solving the hydrogen embrittlement problem has many disadvantages such as low coating material life, high cost, difficulty in large-scale application, and high requirements for hydrogen purity. Related research on hydrogen embrittlement sensitive areas is also not mature. Therefore, there is an urgent need for a hydrogen embrittlement prevention method for hydrogen embrittlement sensitive welding areas. Summary of the invention

[0005] In view of the above problems, the purpose of the present invention is to provide a coating self-repair method and application for hydrogen pipelines.

[0006] One of the present inventions provides a coating self-repair method for a hydrogen pipeline, which comprises the following steps:

[0007] 1) preparing an aluminum coating and an aluminum oxide coating on the outer surface of the welding area of ​​the hydrogen transmission pipeline from the inside to the outside in order to form a self-repairing hydrogen barrier coating;

[0008] 2) Introducing oxygen-doped hydrogen into the hydrogen transmission pipeline to complete the self-repairing process of the self-repairing hydrogen barrier coating.

[0009] According to a specific embodiment of the present invention, the outer surface of the welding area is a cylindrical curved surface 1;

[0010] Preferably, the cylindrical curved surface 1 is the outer surface of the hydrogen pipeline between the plane 4 and the plane 5 obtained by equidistantly translating the plane 3 where the weld 2 is located left and right along the central axis of the hydrogen pipeline;

[0011] Preferably, the width of the cylindrical curved surface is 5 to 20 cm.

[0012] In the present invention, considering that the weld and the weld heat affected zone are the areas with greater hydrogen embrittlement sensitivity in the hydrogen pipeline, the weld area referred to in the present invention includes not only the weld, but also the weld heat affected zone around the weld during welding. The weld is a weld obtained by welding the hydrogen pipelines in a manner including but not limited to metal arc welding (SMAW), submerged arc welding (SAW), gas tungsten arc welding (GTAW) or gas metal arc welding (GMAW).

[0013] According to a specific embodiment of the present invention, the maximum thickness of the aluminum coating is 50 to 1000 μm; and / or

[0014] The thickness of the aluminum oxide coating is 10 to 100 μm; and / or

[0015] The maximum thickness of the self-repairing hydrogen barrier coating is 50 to 1100 μm;

[0016] Preferably, the thickness of the aluminum oxide coating is 10 to 50 μm; and / or

[0017] The maximum thickness of the self-healing coating is 100 to 1050 μm.

[0018] In the present invention, considering that when the thickness of the aluminum coating is too small, it is impossible to provide enough raw aluminum for the self-repairing process; when the thickness of the aluminum coating is too large, it is seriously affected by the gas erosion in the pipeline, which easily leads to accelerated wear of the overall self-repairing hydrogen barrier coating, so the thickness of the aluminum coating is limited. In addition, considering that the thickness of the pipe wall in the welding area is not uniform, especially the thickness of the pipe wall at the weld is higher than the non-weld area in the welding area due to the welding process, the aluminum thickness in the welding area should be uniformly transitioned, with a maximum thickness of 50 to 1000μm and a minimum thickness of about 1μm, so the overall thickness of the aluminum coating is limited to 1 to 1000μm.

[0019] According to a specific embodiment of the present invention, the oxygen-doped hydrogen gas is a mixed gas of oxygen and hydrogen;

[0020] Preferably, the volume of hydrogen in the oxygen-doped hydrogen is taken as 100%, and the volume concentration of oxygen in the oxygen-doped hydrogen is 0.1 to 1000 vppm.

[0021] According to a specific embodiment of the present invention, the purity of hydrogen in the oxygen-doped hydrogen is not less than 99%;

[0022] Preferably, the hydrogen is produced by water electrolysis or fossil fuel hydrogen production;

[0023] Preferably, the oxygen and hydrogen in the oxygen-doped hydrogen are both derived from a hydrogen production method using water electrolysis.

[0024] According to a specific embodiment of the present invention, in step 1), aluminum powder is sprayed on the outer surface of the welding area of ​​the hydrogen transmission pipeline to form the aluminum coating;

[0025] Preferably, the spraying is thermal spraying or electrostatic spraying; and / or the particle size of the aluminum powder is 10 to 50 μm;

[0026] Preferably, the conditions for thermal spraying are as follows: the heat source is an arc, a plasma beam or a flame; and / or the working temperature of the aluminum powder is 200 to 400° C.;

[0027] Preferably, the thermal spraying is performed by a plasma spray gun; and / or the moving speed of the plasma spray gun is 300 to 400 mm / min; and / or the powder feeding gas flow rate is 500 to 800 L / Hr;

[0028] Preferably, the conditions for the electrostatic spraying are as follows: temperature 150 to 250° C.; and / or atomization pressure 0.3 to 0.45 MPa; and / or electrostatic current 10 to 20 μA.

[0029] According to a specific embodiment of the present invention, in step 1), the outer surface of the welding area is pretreated first, and then the aluminum coating is sprayed;

[0030] Preferably, the pretreatment is to first use a sodium hydroxide reagent (such as a 10wt% sodium hydroxide aqueous solution) to remove oxides on the outer surface of the welding area, dry it, and then use sandpaper to roughen the outer surface of the welding area or perform sandblasting to facilitate spraying of the aluminum coating.

[0031] According to a specific embodiment of the present invention, in the sandblasting process, compressed air is used as a driving force, and corundum is selected as a spray material to spray the outer surface of the welding area at a high speed;

[0032] Preferably, the sandblasting is performed using a spray gun; and / or the discharge port of the spray gun is 5 to 10 cm away from the outer surface of the welding area;

[0033] Preferably, after the sandblasting, compressed air is used to blow away impurities, followed by washing with an acetone solution to further remove impurities, and drying with an electric blower for 1 hour;

[0034] Preferably, in order to prevent surface oxidation, the spraying of the aluminum coating is completed within 1 hour after the sandblasting is completed.

[0035] According to a specific embodiment of the present invention, in step 1), the aluminum oxide coating is prepared by plasma spraying or oxidation.

[0036] According to a specific embodiment of the present invention, in step 1), the aluminum oxide coating is prepared by plasma spraying;

[0037] Preferably, the plasma spraying is atmospheric plasma spraying (APS) technology; and / or the spraying power is 30 to 50 kW; and / or the feeding rate of the aluminum oxide powder is 20 to 50 g / min; and / or the spraying distance is 80 to 120 mm.

[0038] According to a specific embodiment of the present invention, in step 1), the aluminum oxide coating is prepared by an oxidation method;

[0039] Preferably, the aluminum coating is heated (at a temperature of 100 to 500° C.) by a heat source (such as an electric arc or a flame) in an air environment to produce the aluminum oxide coating.

[0040] According to a specific embodiment of the present invention, in step 2), the self-repairing process is that the oxygen in the oxygen-doped hydrogen oxidizes the aluminum coating to form aluminum oxide;

[0041] Preferably, when the hydrogen in the oxygen-doped hydrogen is hydrogen produced by water electrolysis, since the hydrogen produced by water electrolysis contains diffused oxygen molecule impurities, the self-repair process can be started without adding additional oxygen thereto;

[0042] Preferably, when the hydrogen in the oxygen-doped hydrogen is produced by a fossil fuel hydrogen production method, oxygen is added to the produced hydrogen regularly (for example, every year or every 2 years) (each oxygen addition lasts for 5 to 20 hours), the volume of hydrogen in the oxygen-doped hydrogen is calculated as 100%, and the volume concentration of oxygen is 0.1 to 1000 vppm to start the self-repair process.

[0043] According to a specific embodiment of the present invention, the hydrogen pipeline is made of X52 pipeline steel, X60 pipeline steel, X70 pipeline steel, X80 pipeline steel, L245 pipeline steel, L360 pipeline steel or 316L stainless steel.

[0044] The method according to the present invention is applied to the prevention of hydrogen embrittlement in hydrogen transmission pipelines, and particularly applied to the prevention of hydrogen embrittlement in pure hydrogen pipelines.

[0045] Beneficial effects of the present invention:

[0046] In view of the problem that the prior art lacks hydrogen embrittlement prevention technology for welding areas including welds and welding heat-affected zones, the present invention provides a coating self-repair method and application for hydrogen pipelines. The method provided by the present invention sequentially prepares aluminum coating and aluminum oxide coating from the inside to the outside of the outer surface of the welding area (including welds and welding heat-affected zones) of the hydrogen pipeline to form a self-repairing hydrogen barrier coating; then, during the actual hydrogen transmission process of the hydrogen pipeline, oxygen-doped hydrogen is transported therein to start the self-repair process. Indoor simulation experiments have proved that the fatigue life of specimens with self-healing hydrogen barrier coating and notches made of X80, X60, X70, L245 and L360 pipeline steels and 316L stainless steel materials under oxygen doping levels of 0.1 to 1000 vppm is: 1) extended by 7.3% to 41.1% compared with the fatigue life of specimens with self-healing coating and notches of the corresponding materials under pure hydrogen; 2) maintained at 90.3% to 101% compared with the fatigue life of specimens with self-healing coating and no notches of the corresponding materials under pure hydrogen. It can be seen that in the self-healing process, the added oxygen and the self-healing hydrogen barrier coating work together to prevent hydrogen embrittlement of hydrogen pipelines. In addition, the method provided by the present invention does not need to construct a self-repairing hydrogen barrier coating on the outer surface of all pipelines in the entire hydrogen pipeline system. The self-repairing hydrogen barrier coating is only constructed on the outer surface of the welding area (including welds and welding heat-affected zones) in the hydrogen pipeline that is most sensitive to hydrogen embrittlement. This makes the self-repairing coating have good firmness and is not easy to fall off during the production process. Combined with the input of oxygen-doped hydrogen, the service life of the entire hydrogen pipeline system can be greatly improved, the area that needs to be constructed with the self-repairing hydrogen barrier coating is greatly reduced, and the hydrogen embrittlement prevention cost of the hydrogen pipeline system is reduced. The method provided by the present invention is applied to a pure hydrogen pipeline system for hydrogen production from water electrolysis or a pure hydrogen pipeline system for hydrogen production from fossil fuels, and a service life of the pure hydrogen pipeline system of not less than 50 years can be achieved. BRIEF DESCRIPTION OF THE DRAWINGS

[0047] Figure 1 A schematic diagram of the structure of a self-repairing hydrogen barrier coating prepared on a hydrogen pipeline by the coating self-repair method for a hydrogen pipeline provided by the present invention, wherein from top to bottom are an aluminum oxide coating, an aluminum coating, and a base metal;

[0048] Figure 2 The outer surface of the welding area of ​​the hydrogen pipeline of the present invention is shown, wherein 1 is the cylindrical curved surface, which is the outer surface of the welding area; 2 is the weld; 3 is the plane where the weld is located; 4 is the plane obtained by translating the plane 3 where the weld is located to the left along the central axis 6 of the hydrogen pipeline; 5 is the plane obtained by translating the plane 3 where the weld is located to the right along the central axis 6 of the hydrogen pipeline; d is the width of the cylindrical curved surface;

[0049] Figure 3The experimental results of the reduction of area obtained in Verification Example 2 are shown. DETAILED DESCRIPTION

[0050] The present invention will be further described below in conjunction with examples, but the examples of the present invention are only exemplary descriptions, and the implementation methods do not constitute limitations of the present invention under any circumstances.

[0051] 1. Feasibility verification of a coating self-repair method for hydrogen pipelines provided by the present invention

[0052] Verification Example 1 - Oxygen inhibits hydrogen embrittlement in pure hydrogen pipelines

[0053] Pipeline steel samples of different materials were selected and fatigue tests were carried out under cyclic pressure in a hydrogen environment with different oxygen concentrations to measure the hydrogen embrittlement sensitivity of the pipeline steel samples. The details are as follows.

[0054] (1) Experimental conditions

[0055] Gas environment: air, 100% hydrogen, hydrogen volume as 100%, oxygen volume concentration of 0.1vppm, 1vppm, 10vppm, 1000vppm of oxygen-doped hydrogen;

[0056] Test pressure of pipeline steel: Considering that the normal working pressure of domestic pure hydrogen pipelines is 3 to 5 MPa, the test pressure of pipeline steel is set to 10 MPa;

[0057] (2) Material of pipeline steel: 20# pipeline steel, X52 pipeline steel, X80 pipeline steel;

[0058] (3) Technical indicators: tensile strength, cross-sectional shrinkage, fatigue crack growth rate

[0059] (4) Technical index determination method:

[0060] ⅰDetermination of tensile strength and area reduction

[0061] With reference to GB / T 228-2010 "Metallic Materials Tensile Laboratory Temperature Test Method" and GB / T 34542.2-2018 "Hydrogen Storage and Transportation System Part 2: Test Method for Compatibility of Metallic Materials with Hydrogen Environment", a smooth round rod-shaped specimen made of any of the materials listed in "(2) Pipeline Steel Material" was prepared and placed in the six different gas environments listed in "(1) Experimental Conditions". The specimen was subjected to uniaxial tension at a constant rate in a displacement-controlled manner until the specimen broke. In this process, the maximum stress value of the specimen before breaking is the tensile strength, and the maximum reduction in the cross-sectional area after the specimen broke is the percentage of the original cross-sectional area.

[0062] ⅱ Fatigue crack growth rate determination

[0063] With reference to GB / T 6398-2017 “Metallic materials fatigue test - fatigue crack growth method” and GB / T 34542.2-2018 “Hydrogen storage and transportation system - Part 2: Test method for compatibility of metallic materials with hydrogen environment”, a compact tensile specimen of any pipeline steel in “(2) Material of pipeline steel” is used. First, a sufficiently long and sharp straight pre-crack is made in the air medium. Then, any gas in “(1) Description of experimental conditions” is filled into the test chamber. After standing for 30 minutes, a sine waveform with a force ratio of 0.1 is used to cyclically load the specimen (the force is maintained at 19 kN and the loading frequency is 1 Hz) to carry out fatigue crack testing.

[0064] The test data of tensile strength, cross-sectional shrinkage and fatigue crack growth rate are shown in Table 1.

[0065] Table 1. Tensile strength, area reduction, fatigue crack growth rate

[0066]

[0067]

[0068] It can be seen from Table 1 that within the oxygen doping range of 0.1vppm to 1000vppm, the higher the oxygen concentration, the higher the tensile strength, the higher the cross-sectional shrinkage, the lower the crack growth rate, and the better the hydrogen embrittlement inhibition effect; 0.1vppm to 1vppm oxygen can play a partial hydrogen embrittlement inhibition effect; the tensile strength, cross-sectional shrinkage, and crack growth rate of the 20# pipeline steel sample in an oxygen-doped hydrogen atmosphere with an oxygen doping of 1000vppm are 105%, 98.8%, and 114.3% of those in the air atmosphere, respectively; the tensile strength, cross-sectional shrinkage, and crack growth rate of the X52 pipeline steel sample in an oxygen-doped hydrogen atmosphere with an oxygen doping of 1000vppm are 105%, 98.8%, and 114.3%, respectively, of those in the air atmosphere; The tensile strength, cross-sectional shrinkage, and crack growth rate in the atmosphere of oxygen-doped hydrogen with an oxygen content of 1000vppm are 97.6%, 97.9%, and 92.5% of those in the air atmosphere, respectively; the tensile strength, cross-sectional shrinkage, and crack growth rate of the X80 pipeline steel sample in the atmosphere of oxygen-doped hydrogen with an oxygen content of 1000vppm are 99.1%, 93.3%, and 62.7% of those in the air atmosphere, respectively, proving that the 1000vppm oxygen content has a more obvious inhibitory effect on the hydrogen embrittlement of pure hydrogen pipelines, and can almost completely eliminate hydrogen embrittlement. According to the above analysis, oxygen has a significant inhibitory effect on hydrogen embrittlement at a lower content, can reduce the crack growth rate, and slow down the problem of reduced toughness of pipeline steel caused by hydrogen penetration. Considering that the explosion limit of hydrogen is between 4.0% and 75.6%, and oxygen is relatively active, the oxygen content should not be too high, and can be within the range of 0.1vppm to 1000vppm. At the same time, the content of other components in hydrogen needs to be strictly controlled.

[0069] Verification Example 2 - Pressure increase helps to enhance the effect of oxygen on the inhibition of hydrogen embrittlement of pipeline steel

[0070] The X80 pipeline steel specimens were subjected to a slow strain rate tensile test with constant load, as detailed below.

[0071] (1) Experimental conditions

[0072] Gas environment: air, 100% hydrogen, oxygen-doped hydrogen with the hydrogen volume being 100% and the oxygen volume concentration being 100vppm;

[0073] Experimental pressure of X8 pipeline steel specimen: set the experimental pressure to 30MPa, 50MPa, and 70MPa;

[0074] Experimental temperature: room temperature, to prevent experimental errors caused by low-temperature ductile-brittle transition due to too low temperature;

[0075] (2) Material of pipeline steel: X80 pipeline steel;

[0076] (3) Technical indicators: Sectional shrinkage

[0077] (4) Determination method of cross-sectional shrinkage: With reference to GB / T 228-2010 "Metallic Materials Tensile Laboratory Temperature Test Method" and GB / T 34542.2-2018 "Hydrogen Storage and Transportation System Part 2: Test Method for Compatibility of Metallic Materials with Hydrogen Environment", smooth round bar specimens of X80 pipeline steel are made and placed in different gas environments. Under different experimental pressures, they are subjected to uniaxial stretching at a constant rate in a displacement-controlled manner until the specimen breaks. In this process, the maximum stress value of the specimen before breaking is the tensile strength, and the maximum reduction in cross-sectional area after the specimen breaks is the percentage of the original cross-sectional area. The larger the cross-sectional shrinkage, the higher the toughness and the lower the brittleness of the material. The high cross-sectional shrinkage of the material measured in a hydrogen environment is a key indicator of hydrogen embrittlement resistance.

[0078] The experimental data of the cross-sectional shrinkage rate are recorded in Figure 3 middle.

[0079] Figure 3 The results show that at 30MPa, 50MPa, and 70MPa, the cross-sectional shrinkage of the X80 pipeline steel sample is the highest in air atmosphere, followed by 100vppm oxygen-doped hydrogen atmosphere, and finally hydrogen atmosphere; specifically, at 30MPa, 50MPa, and 70MPa: the cross-sectional shrinkage of the X80 pipeline steel sample in hydrogen atmosphere is 76.1%, 59.4%, and 44.7% of its cross-sectional shrinkage in air atmosphere, and the effect of hydrogen embrittlement on the cross-sectional shrinkage is more obvious; the cross-sectional shrinkage in 100vppm oxygen-doped hydrogen atmosphere is 95.8%, 86.4%, and 95% of its cross-sectional shrinkage in air atmosphere, which is closer to the cross-sectional shrinkage in air atmosphere, and the hydrogen embrittlement inhibition effect is better. Therefore, it can be proved that the hydrogen embrittlement inhibition effect of trace oxygen is applicable to pipeline steel materials.

[0080] Verification Example 3-Alumina coating has hydrogen embrittlement inhibition effect

[0081] Cathodic hydrogen charging test was carried out on X80 pipeline steel specimens constructed with alumina coating, the details of which are as follows.

[0082] (1) Sample: Take two X80 pipeline steel sheets of the same specifications, one of which is used as a non-coated steel sample; the other steel sheet is sandblasted (the purpose is to remove surface dirt, debris, rust and other impurities while increasing the roughness of the steel sheet surface to facilitate the subsequent adhesion of the alumina coating). Specifically: use compressed air as the driving force, select corundum as the spray material for high-speed spraying, and keep the spray gun surface 5 to 10 cm away from the steel sheet. After sandblasting, use compressed air to blow away impurities, then use acetone solution to further remove impurities, and use an electric blower to dry. Dry for 1 hour; to prevent surface oxidation, within 1 hour after the sandblasting step is completed, use a plasma spray gun to spray the aluminum oxide coating with aluminum oxide powder with a purity greater than 99% and an average particle size of 20 μm as a raw material (key technical parameters are: plasma spray gun current 500A, spraying power 50kW, main gas flow 50L / min, spraying distance 10cm, powder feeding rate 25g / min), and finally prepare an aluminum oxide coating with uniform thickness transition and dense structure. The maximum thickness of the prepared aluminum oxide coating is about 100 μm, and a coated steel sample is obtained;

[0083] (2) Technical indicators: hydrogen concentration;

[0084] (3) Technical index determination method: 0.1 mol / L sodium hydroxide solution was used as the electrolyte and 10 mA / cm 2 and 80mA / cm 2 The coated steel sample was charged with hydrogen at a constant current density of , and then the concentration of hydrogen in the coated steel sample was measured and calculated by electrochemical oxidation method; the uncoated steel sample was tested in the same way; the hydrogen concentration was calculated according to Faraday's law with reference to formula 1:

[0085] C H =Q / (zFv) Formula 1

[0086] Wherein, Q is the charge; z is the number of electrons participating in the reaction, which is 1 for hydrogen; F is the Faraday constant, which is 96485C / mol; v represents the sample volume; the experimental results are shown in Table 2.

[0087] Table 2. Cathode hydrogen charging test

[0088]

[0089] From the data in Table 2, it can be seen that when the hydrogen charging current density is the same, the hydrogen concentration in the coated steel sample is much lower than that in the uncoated steel. Specifically: at 10 mA / cm 2 At a hydrogen charging current density of 80 mA / cm, the hydrogen concentration in the coated steel is 16% of that in the uncoated steel; 2At a hydrogen charging current density of , the hydrogen concentration in the coated steel is 28.9% of that in the uncoated steel. This indicates that the aluminum oxide coating on the surface of the coated steel can greatly reduce the amount of hydrogen atoms that penetrate into the metal material, thereby inhibiting the hydrogen embrittlement of the metal material.

[0090] 2. Implementing a coating self-repair method for hydrogen pipelines provided by the present invention

[0091] Example 1

[0092] The coating self-repairing method for hydrogen transmission pipeline provided by the present invention is applied to a pure hydrogen pipeline system for producing hydrogen by electrolysis of water:

[0093] 1) Construction of self-healing hydrogen barrier coating

[0094] A. For the outer surface of the welding area (specifically including the weld and the welding heat affected zone) of the pure hydrogen pipeline system (corresponding to Figure 2 The width d of the cylindrical curved surface is 5 cm) is pretreated: first, a 10 wt % sodium hydroxide aqueous solution is used to remove the oxide on the outer surface of the welding area, and then the outer surface of the welding area is roughened with sandpaper to facilitate the subsequent spraying of the aluminum coating;

[0095] B. preparing an aluminum coating by thermal spraying on the outer surface of the welding area pretreated in step A, specifically, using a plasma beam as a heat source, heating aluminum powder (particle size of 10 to 50 μm, average particle size of 20 μm) to a semi-molten or molten state at a temperature of 300° C., and spraying aluminum onto the outer surface of the pretreated welding area by a plasma spray gun (moving speed of 350 mm / min) with the aid of compressed air with a flow rate of 650 L / Hr, to deposit and form an aluminum coating, wherein the coating thickness gradually increases and evenly transitions from the heat-affected zone of the hydrogen pipeline welding to the weld, with a maximum thickness of 500 μm and a minimum thickness of about 1 μm;

[0096] C. On the basis of the aluminum coating obtained in step B, an aluminum oxide coating is prepared by an oxidation method: a flame is used as a heat source in an air environment, and the outer surface of the aluminum coating is heated at a temperature of 300° C. to prepare an aluminum oxide coating with a thickness of 50 μm, thereby completing the construction of a self-repairing hydrogen barrier coating with a maximum thickness of 550 μm;

[0097] 2) In practical applications, since the hydrogen produced by water electrolysis contains trace amounts of oxygen, it can undergo a self-repair process during the transportation of pure hydrogen.

[0098] After the coating is self-repaired using the method provided by the present invention, the life of the pure hydrogen pipeline for producing hydrogen by electrolyzing water is not less than 50 years.

[0099] Example 2

[0100] The coating self-repairing method for hydrogen pipeline provided by the present invention is applied to the pure hydrogen pipeline system of fossil fuel hydrogen production:

[0101] 1) Construction of self-healing hydrogen barrier coating

[0102] A. The outer surface of the pure hydrogen pipeline welding area (specifically including the weld and the welding heat affected zone) of fossil fuel hydrogen production (corresponding to Figure 2 The width d of the cylindrical curved surface in the middle is 20 cm) for pretreatment: first, a 10wt% sodium hydroxide aqueous solution is used to remove the oxide on the outer surface of the welding area, dry it, and then perform sandblasting to facilitate the subsequent spraying of the aluminum coating; the sandblasting process specifically uses compressed air as a driving force, and uses corundum as a spray material for high-speed spraying. The surface of the spray gun is 7.5 cm away from the outer surface of the welding area. After sandblasting, impurities are blown away by compressed air, and then acetone solution is used to clean and further remove impurities, and an electric blower is used to dry for 1 hour to complete the pretreatment process;

[0103] B. To prevent oxidation of the surface of the pure hydrogen pipeline after pretreatment, an aluminum coating is prepared on the outer surface of the welding area by thermal spraying (using flame as heat source) within 1 hour after the sandblasting step is completed. The specific method is: using oxygen as the combustion-supporting gas, compressed air as the driving gas, a powder feeding rate of 50g / min, a nozzle distance of 100mm from the surface of the welding area, and a spray gun movement speed of 500mm / s, aluminum powder (particle size of 10 to 50μm, average particle size of 20μm) is sprayed on the outer surface of the welding area to form an aluminum coating. The coating thickness gradually increases and evenly transitions from the heat-affected zone of the hydrogen pipeline welding to the weld, with a maximum thickness of 100μm and a minimum thickness of about 1μm;

[0104] C. On the basis of the aluminum coating obtained in step B, an aluminum oxide coating is prepared by a plasma spraying method to construct a self-repairing hydrogen barrier coating: specifically, an atmospheric plasma spraying (APS) technology is used, with a spraying power of 40 kW and an aluminum oxide powder feeding amount of 35 g / min, to spray aluminum oxide powder (particle size of 1 to 100 μm) on the surface of the aluminum coating in the welding area, and an aluminum oxide coating with a thickness of 50 μm is deposited to complete the construction of the self-repairing hydrogen barrier coating, and its maximum thickness is 150 μm;

[0105] 2) In actual applications, repair is carried out once a year. Specifically, 100 vppm of oxygen is added to pure hydrogen each time. The oxygen addition time is 10 hours per time, and the self-repair process is carried out during the pure hydrogen transportation process.

[0106] After the coating is self-repaired using the method provided by the present invention, the life of a pure hydrogen pipeline for producing hydrogen from fossil fuels is not less than 50 years.

[0107] In order to facilitate subsequent experimental evaluation and demonstrate the self-repairing process, indoor simulation embodiments 3 to 9 and comparative examples 1 and 2 are provided.

[0108] Building a self-healing hydrogen barrier coating

[0109] Example 3

[0110] Arc welding was used to weld two smooth round bar samples made of X52 pipeline steel together to form the outer surface of the welding area to be treated (including the weld and the welding heat affected zone) (corresponding to Figure 2 The width d of the middle cylindrical surface is 5 cm);

[0111] A. The outer surface of the welding area is treated with a sodium hydroxide reagent (specifically, a 10wt% sodium hydroxide aqueous solution) to remove surface pollutants, and then sandblasting is performed: compressed air is used as a driving force, and corundum is selected as a spray material for high-speed spraying, and the discharge port of the spray gun is 5cm away from the outer surface of the welding area; after the sandblasting is completed, impurities are blown away by compressed air, and then acetone solution is used for further cleaning and impurities are removed, and an electric heat blower is used to dry for 1h to complete the pretreatment process;

[0112] B. Preheat the outer surface of the welding area at 100°C, then use an arc as a heat source to heat aluminum powder (particle size of 10 to 50 μm, average particle size of 20 μm) to a semi-molten state at a temperature of 300°C, and then use a plasma spray gun at a moving speed of 300 mm / min and a flow rate of 800 L / Hr of compressed air to spray aluminum onto the pretreated outer surface of the welding area to deposit and form an aluminum coating. The coating thickness gradually increases and transitions evenly from the welding heat affected zone to the weld, with a maximum thickness of 1000 μm and a minimum thickness of about 1 μm;

[0113] C. An oxidation method is used to oxidize the aluminum coating obtained in step B to produce an aluminum oxide coating, and a self-repairing hydrogen barrier coating is constructed for use. The specific steps are: clean the surface of the aluminum coating, use an arc spray gun to heat the aluminum coating in an air environment, and control the temperature at 300°C; move the spray gun back and forth to heat the surface of the aluminum coating evenly to form an aluminum oxide coating with a thickness of 50μm, complete the construction of the self-repairing hydrogen barrier coating, and its maximum thickness is 1050μm, and obtain sample 1.

[0114] Example 4

[0115] Submerged arc welding was used to weld two smooth round bar samples made of X60 pipeline steel together to form the outer surface of the welding area to be treated (including the weld and the welding heat affected zone) (corresponding to Figure 2 The width d of the middle cylindrical surface is 5 cm);

[0116] A. The outer surface of the welding area is treated with a sodium hydroxide reagent (specifically a 10 wt % sodium hydroxide aqueous solution) to remove surface contaminants, and then the outer surface of the welding area is roughened with sandpaper for subsequent spraying of an aluminum coating;

[0117] B. Control the ambient humidity at 50% to ensure that the ambient humidity for spraying is appropriate; then pour the spray filler (specifically aluminum powder with a particle size of 10 to 50 μm and an average particle size of 20 μm) into the spray gun, adjust the spray distance and spray angle of the spray gun, and keep the spray speed moderate; then electrostatic spraying is performed under the conditions of a temperature of 250°C, an atomization pressure of 0.45 MPa, and an electrostatic current of 20 μA; after the spraying is completed, clean the spraying equipment, remove the residual paint, and obtain an aluminum coating, the coating thickness gradually increases from the welding heat affected zone to the weld and transitions evenly, the maximum thickness is 500 μm, the minimum thickness is about 1 μm, and the minimum thickness is about 1 μm;

[0118] C. The aluminum coating surface obtained in step B is sprayed with an aluminum oxide coating using atmospheric plasma spraying (APS) technology. The specific steps are as follows: clean the aluminum coating surface, open the gas cylinder, adjust the argon protection pressure to 0.6 MPa, set the spray gun travel program, start the operation, start the spray gun arcing, and after the plasma flame is stable, turn on the powder feeding gas switch, adjust the powder feeding amount to 40 g / min, spray aluminum oxide powder (particle size of 1 to 100 μm) on the surface of the aluminum coating in the welding area at a spraying power of 30 kW and a spraying distance of 80 mm to deposit an aluminum oxide coating with a thickness of 50 μm. After completion, stop feeding powder, turn off argon, reduce working current, and turn off power to complete the construction of the self-repairing hydrogen barrier coating with a maximum thickness of 550 μm, and obtain sample 2.

[0119] Example 5

[0120] Two smooth round bar samples made of X70 pipeline steel were welded together by gas tungsten arc welding to form the outer surface of the welding area to be processed (including the weld and the welding heat affected zone) (corresponding to Figure 2 The width d of the middle cylindrical surface is 5 cm);

[0121] A. The outer surface of the welding area is treated with a sodium hydroxide reagent (specifically, a 10wt% sodium hydroxide aqueous solution) to remove surface pollutants, and then sandblasting is performed: compressed air is used as a driving force, and corundum is selected as a spray material for high-speed spraying, and the surface of the spray gun outlet is 5cm away from the outer surface of the welding area; after the sandblasting is completed, impurities are blown away by compressed air, and then acetone solution is used for further cleaning and impurities are removed, and an electric blower is used to dry for 1h to complete the pretreatment process;

[0122] B. Preheat the outer surface of the welding area at 100°C, and then perform thermal spraying: using a plasma beam as a heat source, heat aluminum powder (particle size of 10 to 50 μm, average particle size of 20 μm) to a semi-molten state at a temperature of 300°C, and spray aluminum onto the outer surface of the pretreated welding area through a plasma spray gun at a moving speed of 320 mm / min and with the help of compressed air with a flow rate of 760 L / Hr, to deposit and form an aluminum coating. The coating thickness gradually increases and transitions evenly from the welding heat affected zone to the weld, with a maximum thickness of 800 μm and a minimum thickness of about 1 μm;

[0123] C. The aluminum coating surface obtained in step B is sprayed with an aluminum oxide coating using atmospheric plasma spraying (APS) technology. The specific steps are as follows: clean the aluminum coating surface, open the gas cylinder, adjust the argon protection pressure to 0.6 MPa, set the spray gun travel program, start the operation, start the spray gun arcing, and after the plasma flame is stable, turn on the powder feeding gas switch, adjust the powder feeding amount to 40 g / min, and spray aluminum oxide powder (particle size of 1 to 100 μm) on the surface of the aluminum coating in the welding area at a spraying power of 50 kW and a spraying distance of 120 mm to deposit an aluminum oxide coating with a thickness of 50 μm. After completion, stop feeding powder, turn off argon, reduce the working current, and turn off the power to complete the construction of the self-repairing hydrogen barrier coating with a maximum thickness of 850 μm, and obtain sample 3.

[0124] Example 6

[0125] Two smooth round bar samples made of L245 pipeline steel were welded together by metal arc welding to form the outer surface of the welding area to be treated (including the weld and the welding heat affected zone) (corresponding to Figure 2 The width d of the middle cylindrical surface is 5 cm);

[0126] A. The outer surface of the welding area is treated with a sodium hydroxide reagent (specifically a 10 wt % sodium hydroxide aqueous solution) to remove surface contaminants, and then the outer surface of the welding area is roughened with sandpaper to facilitate subsequent spraying of an aluminum coating;

[0127] B. Control the ambient humidity at 50% to ensure that the ambient humidity of the spraying environment is appropriate; then pour the spray filler (specifically aluminum powder with an average particle size of 20 μm) into the spray gun, adjust the spray distance and spray angle of the spray gun, and keep the spray speed moderate; then electrostatic spraying is performed under the conditions of a temperature of 150°C, an atomization pressure of 0.3MPa, and an electrostatic current of 10μA; after the spraying is completed, clean the spraying equipment, remove the residual paint, and prepare an aluminum coating, the coating thickness gradually increases from the welding heat affected zone to the weld and transitions evenly, the maximum thickness is 50μm, and the minimum thickness is about 1μm;

[0128] C. An oxidation method is used to oxidize the aluminum coating obtained in step B to produce an aluminum oxide coating, and a self-repairing hydrogen barrier coating is constructed for use. The specific steps are: clean the surface of the aluminum coating, use a flame spray gun to heat the aluminum coating in an air environment, and control the temperature at 300°C; move the spray gun back and forth to heat the surface of the aluminum coating evenly to form an aluminum oxide coating with a thickness of 50μm, complete the construction of the self-repairing hydrogen barrier coating, and its maximum thickness is 100μm, and obtain sample 4.

[0129] Example 7

[0130] Two smooth round bar samples made of L360 pipeline steel were welded together by arc welding to form the outer surface of the welding area to be treated (including the weld and the welding heat affected zone) (corresponding to Figure 2 The width d of the middle cylindrical surface is 5 cm);

[0131] A. The outer surface of the welding area is treated with a sodium hydroxide reagent (specifically, a 10wt% sodium hydroxide aqueous solution) to remove surface pollutants, and then sandblasting is performed: compressed air is used as a driving force, and corundum is selected as a spray material for high-speed spraying, and the discharge port of the spray gun is 5cm away from the outer surface of the welding area; after the sandblasting is completed, impurities are blown away by compressed air, and then acetone solution is used for further cleaning and impurities are removed, and an electric heat blower is used to dry for 1h to complete the pretreatment process;

[0132] B. Preheat the outer surface of the welding area at 100°C, and then perform thermal spraying: Using flame as a heat source, heat aluminum powder (particle size of 10 to 50 μm, average particle size of 20 μm) to a semi-molten state at 300°C, and spray aluminum onto the outer surface of the pretreated welding area through a plasma spray gun at a moving speed of 355 mm / min and with the help of compressed air with a flow rate of 625 L / Hr, to deposit and form an aluminum coating. The coating thickness gradually increases and transitions evenly from the welding heat affected zone to the weld, with a maximum thickness of 500 μm and a minimum thickness of about 1 μm;

[0133] C. An oxidation method is used to oxidize the aluminum coating obtained in step B to produce an aluminum oxide coating, and a self-repairing hydrogen barrier coating is constructed for use. The specific steps are: clean the surface of the aluminum coating, use a flame spray gun to heat the aluminum coating in an air environment, and control the temperature at 300°C; move the spray gun back and forth to heat the surface of the aluminum coating evenly to form an aluminum oxide coating with a thickness of 10μm, complete the construction of the self-repairing hydrogen barrier coating, and its maximum thickness is 510μm, and obtain sample 5.

[0134] Example 8

[0135] Submerged arc welding was used to weld two smooth round rod samples made of 316L stainless steel together to form the outer surface of the welding area to be processed (including the weld and the welding heat affected zone) (corresponding to Figure 2 The width d of the middle cylindrical surface is 5 cm);

[0136] A. The outer surface of the welding area is treated with a sodium hydroxide reagent (specifically, a 10wt% sodium hydroxide aqueous solution) to remove surface pollutants, and then sandblasting is performed: compressed air is used as a driving force, and corundum is selected as a spray material for high-speed spraying, and the discharge port of the spray gun is 5cm away from the outer surface of the welding area; after the sandblasting is completed, impurities are blown away by compressed air, and then acetone solution is used for further cleaning and impurities are removed, and an electric heat blower is used to dry for 1h to complete the pretreatment process;

[0137] B. Preheat the outer surface of the welding area at 100°C, and then perform thermal spraying: using a plasma beam as a heat source, heat aluminum powder (particle size of 10 to 50 μm, average particle size of 20 μm) to a semi-molten state at a temperature of 300°C, and spray aluminum onto the outer surface of the pretreated welding area through a plasma spray gun at a moving speed of 400 mm / min and with the help of compressed air with a flow rate of 500 L / Hr, to deposit and form an aluminum coating. The coating thickness gradually increases and transitions evenly from the welding heat affected zone to the weld, with a maximum thickness of 100 μm and a minimum thickness of about 1 μm;

[0138] C. An oxidation method is used to oxidize the aluminum coating obtained in step B to produce an aluminum oxide coating, and a self-repairing hydrogen barrier coating is constructed for use. The specific steps are: clean the surface of the aluminum coating, use a flame spray gun to heat the aluminum coating in an air environment, and control the temperature at 300°C; move the spray gun back and forth to heat the surface of the aluminum coating evenly to form an aluminum oxide coating with a thickness of 50μm, complete the construction of the self-repairing hydrogen barrier coating, and its maximum thickness is 150μm, and obtain sample 6.

[0139] Example 9

[0140] Submerged arc welding was used to weld two smooth round bar samples made of X80 pipeline steel together to form the outer surface of the welding area to be treated (including the weld and the welding heat affected zone) (corresponding to Figure 2 The width d of the middle cylindrical surface is 5 cm);

[0141] A. The outer surface of the welding area is treated with a sodium hydroxide reagent (specifically, a 10wt% sodium hydroxide aqueous solution) to remove surface pollutants, and then sandblasting is performed: compressed air is used as a driving force, and corundum is selected as a spray material for high-speed spraying, and the discharge port of the spray gun is 5cm away from the outer surface of the welding area; after the sandblasting is completed, impurities are blown away by compressed air, and then acetone solution is used for further cleaning and impurities are removed, and an electric heat blower is used to dry for 1h to complete the pretreatment process;

[0142] B. Preheat the outer surface of the welding area at 100°C, then use an arc as a heat source to heat aluminum powder (particle size of 10 to 50 μm, average particle size of 20 μm) to a semi-molten state at a temperature of 300°C, and then use a plasma spray gun at a moving speed of 360 mm / min and a flow rate of 630 L / Hr of compressed air to spray aluminum onto the pretreated outer surface of the welding area to deposit and form an aluminum coating. The coating thickness gradually increases and transitions evenly from the welding heat affected zone to the weld, with a maximum thickness of 500 μm and a minimum thickness of about 1 μm;

[0143] C. An oxidation method is used to oxidize the aluminum coating obtained in step B to produce an aluminum oxide coating, and a self-repairing hydrogen barrier coating is constructed for use. The specific steps are: clean the surface of the aluminum coating, use a flame spray gun to heat the aluminum coating in an air environment, and control the temperature at 300°C; move the spray gun back and forth to heat the surface of the aluminum coating evenly to form an aluminum oxide coating with a thickness of 50μm, completing the construction of the self-repairing hydrogen barrier coating, and its maximum thickness is 550μm to obtain sample 7.

[0144] Comparative Example 1

[0145] Two smooth round rod samples made of X80 pipeline steel were welded together by submerged arc welding as comparison sample 1.

[0146] Comparative Example 2

[0147] Construction of aluminum oxide coating: According to the same method as Example 7, only an aluminum oxide coating of equal thickness was constructed to obtain comparative sample 2.

[0148] Self-repairing process and self-repairing effect evaluation of Examples 3 to 9 and Comparative Examples 1 and 2

[0149] Take 3 samples of each of the samples 1 to 7 prepared in Examples 3 to 9 and Comparative Examples 1 and 2, take 1 sample of Comparative Sample 1, and take 2 samples of Comparative Sample 2, and refer to GB / T 34542.2-2018 "Hydrogen Storage and Transportation System Part 2: Test Method for Compatibility of Metallic Materials with Hydrogen Environment" and GB / T 3075-2008 "Axial force control method for fatigue test of metallic materials", three samples 1 (numbered 1-1 to 1-3), three samples 2 (numbered 2-1 to 2-3), three samples 3 (numbered 3-1 to 3-3), three samples 4 (numbered 4-1 to 4-3), three samples 5 (numbered 5-1 to 5-3), three samples 6 (numbered 6-1 to 6-3), three samples 7 (numbered 7-1 to 7-3), one comparison sample 1 (numbered D1-1), and two comparison samples 2 (numbered D2-1 to D2-2) were placed in oxygen-doped hydrogen with different oxygen contents for self-repair process. While the self-repair process was being carried out, an in-situ fatigue life test was carried out with a force ratio of 0.1 and a sinusoidal loading waveform. Constant load control was adopted. The fatigue life of the sample to be tested was tested when the sample was pulled apart, and the fracture morphology was observed.

[0150] The sample numbers, corresponding experimental variables and experimental results are shown in Table 3, where the notch is a V-shaped notch with an average size of 70 μm opened on the metal surface or the surface of the alumina coating to simulate the damage caused by gas erosion in actual use of the hydrogen pipeline.

[0151] Table 3. Sample numbers and experimental variable settings for self-repair effect evaluation experiments

[0152]

[0153]

[0154] From the experimental results in Table 3, it can be seen that: first, by comparing No. D1-1 with No. D2-1 and No. D2-2, it can be seen that the alumina coating has an obvious effect of inhibiting hydrogen embrittlement, but when there is a notch in the sample, hydrogen atoms are easy to diffuse from the notch to the steel under the action of tensile stress, resulting in failure of hydrogen embrittlement inhibition; in a pure hydrogen atmosphere without oxygen, the fatigue life of No. 1-2, 2-2, 3-2, 4-2, 5-2, 6-2, and 7-2 with aluminum-alumina coating (i.e., self-healing hydrogen barrier coating) and no notch reaches 69477 to 50293 7 cycles, the fatigue life of No. 1-1, 2-1, 3-1, 4-1, 5-1, 6-1, and 7-1 with aluminum-aluminum oxide coating and notch reached 58032 to 437237 cycles; and compared with sample 5, comparative sample 2 only prepared an aluminum oxide coating of equal thickness according to the same method as sample 5, showing that in a pure hydrogen atmosphere without oxygen doping, the fatigue life of No. D-2-1 (notch) is only 49% of No. 5-1 (notch), and the fatigue life of No. D-2-2 (no notch) is 62% of No. 5-2 (no notch). It can be seen that in the absence of oxygen doping, whether it is notched or notched, the samples with aluminum-aluminum oxide coating can maintain a high fatigue life, and the hydrogen embrittlement inhibition performance of aluminum-aluminum oxide coating is better than that of pure aluminum oxide coating;

[0155] Secondly, under the oxygen doping range of 0.1 to 1000 vppm, the fatigue life of No. 1-3 to 7-3: 1) compared with the fatigue life of No. 1-1 to 7-1, it is extended by 14.8%, 41.1%, 35.5%, 28.5%, 12.8%, 7.3% and 20.9% respectively; 2) compared with No. 1-2 to 7-2, it is 94.2%, 93.9%, 97.9%, 90.3%, 91.1%, 93.3% and 101% of the fatigue life of No. 1-2 to 7-2 respectively, indicating that the aluminum-alumina self- The samples with repaired hydrogen barrier coating can start the self-repair process in an atmosphere of oxygen-doped hydrogen with oxygen content of 0.1 to 1000 vppm. Even if there are openings on the surface, the hydrogen embrittlement phenomenon can be well suppressed. Even compared with 7-2, the fatigue life of the notched sample 7-3 in the atmosphere of oxygen-doped hydrogen with oxygen content of 1000 vppm is slightly higher than the fatigue life of the unnotched sample 7-2 in the atmosphere of pure hydrogen. The self-repair of the aluminum-alumina coating can offset the influence of the notch, successfully suppress the hydrogen embrittlement phenomenon, and show strong hydrogen embrittlement suppression performance.

[0156] On the third aspect, samples 1 to 7 have a higher fatigue life under the conditions of notch and oxygen doping. Under the conditions of no oxygen doping and notch and / or no notch, the fatigue life can reach a minimum of 58032 cycles. It can also be explained that in the self-healing hydrogen barrier coating method provided by the present invention, the coating prepared focusing on the weld area and the welding heat affected zone has good firmness and is not easy to fall off during operation and cause loss of hydrogen barrier protection function. It is also beneficial to the long-term stable operation of chemical production equipment and reduces maintenance costs.

[0157] In summary, combined with the above analysis of Table 3 and the verification results of Verification Examples 1 to 3 above, it can be seen that the coating self-repair method for hydrogen pipelines provided by the present invention is feasible and effective for preventing hydrogen embrittlement problems in hydrogen pipelines (especially pure hydrogen pipelines).

[0158] Although the present invention has been described with reference to specific embodiments, it will be appreciated by those skilled in the art that various changes may be made without departing from the true spirit and scope of the present invention. In addition, the subject matter, spirit and scope of the present invention may be varied to accommodate specific situations, materials, material combinations and methods. All of these changes are included within the scope of the claims of the present invention.

Claims

1. A coating self-repair method for a hydrogen pipeline, comprising the following steps: 1) preparing an aluminum coating and an aluminum oxide coating on the outer surface of the welding area of ​​the hydrogen transmission pipeline from the inside to the outside in order to form a self-repairing hydrogen barrier coating; 2) Introducing oxygen-doped hydrogen into the hydrogen transmission pipeline to complete the self-repairing process of the self-repairing hydrogen barrier coating.

2. The method according to claim 1, characterized in that The outer surface of the welding area is a cylindrical curved surface (1); Preferably, the cylindrical curved surface (1) is the outer surface of the hydrogen pipeline between the plane (4) and the plane (5) obtained by equidistantly translating the plane (3) where the weld (2) is located left and right along the central axis of the hydrogen pipeline; Preferably, the width of the cylindrical curved surface is 5 to 20 cm.

3. The method according to claim 1 or 2, characterized in that: The maximum thickness of the aluminum coating is 50 to 1000 μm; and / or The thickness of the aluminum oxide coating is 10 to 100 μm; and / or The maximum thickness of the self-repairing hydrogen barrier coating is 50 to 1100 μm.

4. The method according to any one of claims 1 to 3, characterized in that The oxygen-doped hydrogen gas is a mixed gas of hydrogen and oxygen; Preferably, the volume of hydrogen in the oxygen-doped hydrogen is taken as 100%, and the volume concentration of oxygen in the oxygen-doped hydrogen is 0.1 to 1000 vppm.

5. The method according to any one of claims 1 to 4, characterized in that The purity of hydrogen in the oxygen-doped hydrogen is not less than 99%; Preferably, the hydrogen is produced by water electrolysis or fossil fuel hydrogen production; Preferably, the oxygen and hydrogen in the oxygen-doped hydrogen are both derived from a hydrogen production method using water electrolysis.

6. The method according to any one of claims 1 to 5, characterized in that In step 1), aluminum powder is sprayed on the outer surface of the welding area of ​​the hydrogen transmission pipeline to form the aluminum coating; Preferably, the spraying is thermal spraying or electrostatic spraying; and / or the particle size of the aluminum powder is 10 to 50 μm.

7. The method according to any one of claims 1 to 6, characterized in that In step 1), the aluminum oxide coating is prepared by plasma spraying or oxidation.

8. The method according to any one of claims 1 to 7, characterized in that In step 2), the self-repairing process is that the oxygen in the oxygen-doped hydrogen gas oxidizes the aluminum coating to form aluminum oxide.

9. The method according to any one of claims 1 to 8, characterized in that The hydrogen transmission pipeline is made of X52 pipeline steel, X60 pipeline steel, X70 pipeline steel, X80 pipeline steel, L245 pipeline steel, L360 pipeline steel or 316L stainless steel.

10. Use of the method according to any one of claims 1 to 9 in preventing hydrogen embrittlement in hydrogen transmission pipelines, in particular in preventing hydrogen embrittlement in pure hydrogen pipelines.